Dinamika Pengaturan Tayangan Televisi Indonesia - Gunawan Witjaksana (Program Studi Ilmu Komunikasi, 2007)
Television has deep impact to the audience, moreover the audience is in the powerless conditions. Indonesia is the real example, that the audience is in the powerless/impowering conditions, on the contrary the television is so powerfull. This condition has to be changed, until reach ballance position when the television considers public interest, producing the good quality programs, public appreciates the programs because of the quality and their need, rating of the programs reach high level, and the advertisers interest to these programs. The goverment dan Indonesian Broadcast Commission (Komisi Penyiaran Indonesia) must work hard together to realise it.